Study on serum estradiol levels in females with Vit D deficiency on Omega-3 fatty acid with vitamin D3 supplementation. - Rajiv Kumar, Mishra; Kanhaiya, Prasad (Journal of Neonatal Surgery, 2025)
Results examining the impact of omega-3 fatty acids (Omega-3FA) and vitamin D3 (VD3) on serum estradiol (E2) are few and contradictory. The impact of VD3 in combination with Omega-3FA on E2 levels has not been examined in any prior research. The purpose of this study was to determine how blood E2 levels in premenopausal females with vitamin D insufficiency (VDD) were affected by VD3, Omega-3FA, and VD3 + Omega-3FA. The purpose of this study was to assess the effects of 300 mg of Omega-3FA taken daily, 50,000 IU of VD3 taken weekly, and their combination over the course of eight weeks. At eight weeks, the mid-follicular serum levels of 25-hydroxy vitamin D (25OHD) and E2 were measured. Four equal study groups were formed from a total of 128 individuals. With the exception of serum calcium (p = 0.045), most measures in the control group did not significantly alter, according to within-group analysis. Serum 25-hydroxyvitamin D (p < 0.001), serum estradiol (p = 0.001), serum calcium (p < 0.001), and serum phosphate (p = 0.043) all showed notable improvements in the VD group. Serum 25-hydroxyvitamin D (p < 0.001), estradiol (p = 0.007), calcium (p = 0.003), phosphate (p = 0.04), and ALT (p = 0.035) all showed significant changes in the Omega-3 FA group. Serum 25-hydroxyvitamin D (p < 0.001), estradiol (p = 0.024), and calcium (p = 0.032) all showed significant changes in the VD plus Omega-3 FA group, whereas PTH, ALT, and urea did not (p > 0.05).The study shows that vitamin D and omega-3 fatty acid supplements, both separately and together, were linked to significant changes in serum levels of calcium, phosphate, estradiol, and 25-hydroxyvitamin D, especially in the intervention groups. By the end of the research, parathyroid hormone levels had not changed significantly. Over the course of the study, indicators related to liver and renal function remained constant. Overall, the results show that certain biochemical indicators were improved by the interventions, and there was no indication of any negative effects on the liver or kidneys during the follow-up period